EKSISTENSI TRANSPORTASI LAUT PADA PELAYARAN RAKYAT - Hermanto, Andy Wahyu (Semarang State University, 2010)
Public sailing is a sub-national marine transportation system that uses a means of motor sailing boat (KLM), motor sailboat (PLM), and plays a role linking the major ports, secondary and tertiary as well as regional and local feeder port. Shipping business management kinship with people using a simple organizational system and not formal, operating a fleet of cruise people did not depend on port infrastructure and can reach remote ports that are difficult to reach by the national shipping. Achievement of productivity about 18% to 20% of total domestic freight (excluding liquid bulk cargo/bulk/special). Approaches and methods used to uncover the extent of the performance of operational feasibility and technical aspects and the role of peoples national shipping is a prototype monitoring field study KLMP 360 GRT on operational performance in the harbor and at the time of sailing. The existence of sea transport shipping people support the development of the central role of regional and local economic activity, and appears to be too influenced by the economic recession. Technical conditions (stability, systems and construction) is generally considered good and have a high level of seaworthiness to sail and meet the standards of the International Maritime Organization (IMO) and ISO 6954 on construction vibration criteria.Pelayaran umum adalah bagian sebuah sistem transportasi laut nasional yang menggunakan sarana Kapal Layar Motor (KLM), Perahu Layar Motor (PLM), dan memainkan peran yang menghubungkan pelabuhan utama, sekunder dan tersier serta pengumpan pelabuhan regional dan lokal . Pengiriman bisnis manajemen kekerabatan dengan orang yang menggunakan sistem organisasi sederhana dan tidak formal, operasi armada pelayaran orang tidak tergantung pada infrastruktur pelabuhan dan dapat mencapai pelabuhan terpencil yang sulit dijangkau oleh pelayaran nasional. Pencapaian produktivitas sekitar 18% sampai 20% dari total angkutan domestik (tidak termasuk kargo curah cair/bulk/khusus). Pendekatan dan metode yang digunakan untuk mengungkap tingkat kinerja operasional dan aspek kelayakan teknis dan peran pelayaran nasional rakyat adalah prototipe pemantauan studi lapangan KLMP 360 GRT mengenai kinerja operasional di pelabuhan dan pada saat berlayar. Keberadaan orang pengiriman transportasi laut mendukung pengembangan peran sentral kegiatan ekonomi regional dan lokal, dan tampaknya terlalu dipengaruhi oleh resesi ekonomi. Kondisi Teknis (stabilitas, sistem dan konstruksi) umumnya dianggap baik dan memiliki tingkat kelayakan yang tinggi untuk berlayar dan memenuhi standar Organisasi Maritim Internasional (IMO) dan ISO 6954 pada kriteria getaran konstruksi.